Wafayat al a’yan wa anba abna al zaman - Abi Al 'Abas Shamsuddin Ahmad Bin Muhammad Bin Abi Bakr Bin Khalkan (Maktabah Al Nahdah Al Misriyyah, 1948)
wd,jil.1,c.1, jil.2,c.1 jil.3,c.1 jil.4,c.1 jil.5,c.1 jil.6,c.1